Nigeria : 2004 Semi-Annual Staff Report Under Intensified Surveillance. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews the 2004 Semiannual IMF Staff Report Under Intensified Surveillance for Nigeria. Overall economic performance in the first half of 2004 was commendable. The implementation of sound macroeconomic policies, underpinned by a conservative reference oil price and savings of the oil revenue windfall, has helped stabilize the economy. Fiscal prudence along with a tight monetary policy has contributed to a buildup of international reserves. Although the outlook for the remainder of 2004 is promising, the government faces the immediate challenge of persuading all states to continue to save the oil revenue windfall.